4c-6-3x=2+5x

Simple and best practice solution for 4c-6-3x=2+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c-6-3x=2+5x equation:


Simplifying
4c + -6 + -3x = 2 + 5x

Reorder the terms:
-6 + 4c + -3x = 2 + 5x

Solving
-6 + 4c + -3x = 2 + 5x

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 4c + 6 + -3x = 2 + 6 + 5x

Reorder the terms:
-6 + 6 + 4c + -3x = 2 + 6 + 5x

Combine like terms: -6 + 6 = 0
0 + 4c + -3x = 2 + 6 + 5x
4c + -3x = 2 + 6 + 5x

Combine like terms: 2 + 6 = 8
4c + -3x = 8 + 5x

Add '3x' to each side of the equation.
4c + -3x + 3x = 8 + 5x + 3x

Combine like terms: -3x + 3x = 0
4c + 0 = 8 + 5x + 3x
4c = 8 + 5x + 3x

Combine like terms: 5x + 3x = 8x
4c = 8 + 8x

Divide each side by '4'.
c = 2 + 2x

Simplifying
c = 2 + 2x

See similar equations:

| x/5=0.41 | | 11X=9X+46 | | Y+6=-5(x+9) | | Y+2=-6(x-7) | | 3z^2+10z+3=0 | | 6x^2+x-75=0 | | -40=-(4v-4)-2(6-6v) | | Y+1=-7(x+2) | | 2+2y+-3=11 | | (2x+3y+1)dx=-(4x+6y-5)dy | | 11v+14x=3450 | | x+2.1x=-26.4 | | y-45+6x=0 | | 16=s/2 | | -2(2x+3)=18 | | -16=4(-v-6)-3(4-8v) | | 6x-3=k(-2x+1) | | 24=-4(1-7n)+7(n+4) | | -4(5x-7)=168 | | 8k+54=-14 | | -328=-8(-7x-7)+8 | | 10x^2+120x-36=0 | | 16x=2x+84 | | (4-8x)2+(x)2=400 | | 81=-5(1-8a)+3a | | 12x+6=100 | | -7(5k-6)=-168 | | 8m-14=59 | | 130=4c+225 | | -5(-7v+8)=-215 | | sin(x)(sin(x)+1)=0 | | -138=6(1+4b) |

Equations solver categories